Comparison of Antropometry and Physical Abilities between Trained and Untrained Individuals in Second Growth Phase - Akbar, Idzam Kholid; Purwanto, Bambang; Setijono, Hari (Folia Medica Indonesiana, 2019)
Evaluations on Plasma Prothrombin Time (PPT) and Activated Partial Thromboplastin Time (APTT) are required in patients with Chronic Kidney Disease (CKD) stage V to determine the risk of bleeding after hemodialysis (HD) using heparin as the anticoagulant. This study aimed to compare the results of PPT and APTT in pre and post-hemodialysis patients with minimum dose of heparin. This was an observational-analytical study with cross-sectional design. The samples were collected in HD wards of Dr. Soetomo Hospital, Surabaya. There were 50 PPT and APTT samples collected from June to August 2017. The samples were evaluated using the tool CoaDATA 501. The examination of coagulation study was conducted in Clinical Pathology Laboratory of Dr. Soetomo Hospital, Surabaya. Paired t-test and Wilcoxon signed-rank test were performed in this study. In the 50 samples, pre-hemodialysis PPT ranged between 10.2-17.6 with the mean of 12.6±2.03 seconds, while for post-hemodialysis, the range was 10.1-20.9 with the mean of 13.41±2.43 seconds. Pre-hemodialysis APPT ranged between 19.5-75.2 with the mean of 30.32±10.43 seconds, while in post hemodialysis the range was 22.21-175 with the mean of 37.52±26.40 seconds. The results of PTT evaluation in pre and post-HD showed no significant difference (p=0.083), while those of APTT showed a significant difference (p=0.035 or p<0.05). Prolongation of APTT in post-HD is due to the use of heparin as an anticoagulant that increases PPT and APTT by inhibiting antithrombin III. HD procedures cause decreased activity of coagulation factors II, IX, X, XII leading to APTT prolongation in post-HD. A significant APTT prolongation was found in post-HD patients with CKD V.